Sustainable development vs. sustainable biosphere - Rolston, Holmes, 1932-2025, author; Ria University Press, publisher (Colorado State University. Libraries, 2010)
In sustainability debates, there are two poles, complements yet opposites. Economy can be prioritized, with the environment contributory to economics at the center. This is sustainable development, widely advocated, including statements by the United Nations. At the other pole, the environment is prioritized. A sustainable biosphere model demands a baseline quality of environment, respect for the integrity of natural systems. The economy must be worked out within such quality of life in a quality environment. This is advocated by the Ecological Society of America. Neither economics nor ecology is well equipped to analyze this issue ethically.
Originally a lecture given at the American Association for the Advancement of Science, Annual Meeting, 2009, Chicago: Our Planet and Its Life: Origins and Futures.
Keywords: sustainable biosphere; environmental conservation; sustainability; United Nations conference on environment and development; UNCED; sustainable development; Ecological Society of America